Study the heat transfer potentiality of a building envelope integrated with Elt at foundation. - Eusuf, Muhammad Abu; al- hasan , Abdullah (IDOSI Publication, 2013)
The aim of this paper is to investigate the heat transfer potentiality of a building envelope integrated with ELT (end-of-life tyres) at foundation. A hazardous waste, ELT or massive scraped tyre waste created environmental load to the local environment. Today, when researchers think of the environmental impacts of tyres, they mostly focus on the management of tyres at the end of their useful lives. From Global perspective it is found that one billion tyres reach the end of their useful lives annually, out of which about four billion ELTs are currently in landfills and as stockpiles worldwide. Study revealed that most of the developing countries currently are not experienced with the disposal method of ELT. Besides, developed countries from Europe, USA, Japan and Singapore have framed specific law or regulation to the disposal of ELT. Recently it is obvious that should find out alternative ways as to reduce the load of massive ELT waste. Furthermore, this study has been designed to manage ELTs massive waste, experimentally. This research followed by an effective experimental set up to observe the real phenomena of ELT for passive cooling in hot humid and tropical climate and make comparison with conventional construction materials and systems